Dynamic Stress Analysis of the Leg Joints of Self-Elevating Platform - 黄曌宇 唐文勇 汪怡 王文涛 (China ocean engineering, 2011)
Since a self-elevating platform often works in water for a long time, the lattice leg is largely influenced by wave and current. The amplitude of leg joint stresses is a very important factor for the fatigue life of the platform. However, there are not many researches having been done on the mechanism and dynamic stress analysis of these leg joints. This paper focuses on the dynamic stress analysis and suppression methods of the leg joints of self-elevating platforms. Firstly, the dynamic stresses of the lattice leg joints are analyzed for a self-elevating platform by use of the 5th-order Stokes wave theory. Secondly, the axial and bending stresses are studied due to their large contributions to total stresses. And then, different joint types are considered and the leg-hull interface stiffness is analyzed for the improvement of the joint dynamic stress amplitude. Finally, some useful conclusions are drawn for the optimization design of the self-elevating platform.